Economic impact of aquaculture in floodplains - a case study of Sonmar Chaur in Bihar, India - Kumar, Raushan; Kumar, Nalini Ranjan; Katiha, P. K.; Krishnan, M.; Prakash, Satya; Kumar, Manoj (Indian Journal of Fisheries, 2016)
Chaurs are shallow water logged areas and have limited scope for agriculture, but can be better utilised for agriculture cum fish production. About 70% (28.34 ha) area of Sonmar chaur in Bihar has been converted into small ponds for aquaculture purposes. Income and employment generated from the chaur from both agriculture and fisheries and fish disposal pattern were studied. The study revealed aquaculture as most profitable enterprise `3,28,000 ha-1) with BC ratio 1.46 followed by agriculture (`37,900 ha-1) and culture based fisheries (`34,400 ha-1) with B-C ratio 2.1 and 2.6, respectively. Maximum employment was generated from aquaculture (1411 man days ha-1) followed by culture based fisheries (70 man days ha-1) and agriculture (35 man days ha-1). The higher employment generation in culture fisheries was mainly due to requirement for watch and ward. The fish was sold either directly to the ultimate consumers or through the vendors. Among the two marketing channels operatings Channel-I in which producer sells directly to consumers was found more efficient (69.7). Though, aquaculture was more profitable and generated higher employment, it requires much higher resources for its practice which may hinder small holders to adopt such practice and also it may impact certain indirect uses of these water bodies. Environmental impact assessment and support to small farmers are needed to utilise such water bodies through aquaculture.